2009
DOI: 10.3171/2009.6.focus09126
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation

Abstract: Vagus nerve stimulation (VNS) is a key tool in the treatment of patients with medically refractory epilepsy. Although the mechanism of action of VNS remains poorly understood, this modality is now the most widely used nonpharmacological treatment for drug-resistant epilepsy. The goal of this work is to review the history of VNS and provide information on recent advances and applications of this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 35 publications
0
37
0
3
Order By: Relevance
“…10,11,14 Studies in the 1990s demonstrated a mean 25%-30% decrease in seizure frequency in epilepsy patients following VNS, which led to US FDA approval in 1997 for the treatment of intractable partial epilepsy in patients older than 12 years of age. 4,9,21 To date, many more retrospective and nonrandomized studies have confirmed the effectiveness of VNS in children 7 and adults afflicted with treatment-resistant epilepsy.…”
mentioning
confidence: 99%
“…10,11,14 Studies in the 1990s demonstrated a mean 25%-30% decrease in seizure frequency in epilepsy patients following VNS, which led to US FDA approval in 1997 for the treatment of intractable partial epilepsy in patients older than 12 years of age. 4,9,21 To date, many more retrospective and nonrandomized studies have confirmed the effectiveness of VNS in children 7 and adults afflicted with treatment-resistant epilepsy.…”
mentioning
confidence: 99%
“…The ability of such external excitatory stimuli to terminate seizures and/or paroxysmal activity may depend upon identifiable parameters, which, at present, are not understood. 10,11,[21][22][23][24][25] In this work, we present two models of brain function, particularly of working memory, although they may be interpreted more broadly as producing activity involved and useful for many cognitive and motor functions. We examine the models' nonlinear dynamic behavior in normal (i.e., working memory) and pathological (i.e., seizure) states.…”
Section: Introductionmentioning
confidence: 99%
“…Since the U.S. Food and Drug Administration approved this device for refractory epilepsy in adult and adolescents in July 1997, this modality is the most widely used nonpharmacological treatment for drug-resistant epilepsy now. However, the underlying mechanisms of VNS remain poorly understood [27]. Other neuromodulation methods, such as chronic anterior thalamic stimulation [28], and responsive neurostimulator [29] are under clinical trials and have shown promising efficacy preliminarily.…”
Section: Different Categories Of Epilepsy Surgerymentioning
confidence: 99%